2015
DOI: 10.1016/s1348-8643(15)00016-6
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies communication in oral biofilm: An ocean of information

Abstract: The diversity of signalling opportunities within microbial communities, and the significant role of these molecules in coordinating gene expression and promoting biofilm formation, has provided the impetus to investigate the potential of inhibitory analogues to disrupt these networks, thereby providing mechanisms to control or influence the development of dental plaque. Within the oral biofilms, resident bacterial cells interact with one another and exchange messages in the form of signalling molecules and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“… 235 , 236 Primary colonizers are primarily gram‐positive cocci and rods, especially Streptococcus species, such as S salivarius . 237 Traditional models of microbial biofilm succession follow a sequential process in which the initial attachment of primary colonizers, namely Streptococcus, Actinomyces, Gemella, Veillonella, Rothia, and Neisseria species, bind to dental pellicle and facilitate subsequent colonization by F nucleatum , which functions as a bridging species between early and late colonizers. 235 From approximately 18 hours to 4 days following colonization of dental biofilm, primary colonizers remain the predominant species among biofilm communities.…”
Section: Plaque Formation and Periodontal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“… 235 , 236 Primary colonizers are primarily gram‐positive cocci and rods, especially Streptococcus species, such as S salivarius . 237 Traditional models of microbial biofilm succession follow a sequential process in which the initial attachment of primary colonizers, namely Streptococcus, Actinomyces, Gemella, Veillonella, Rothia, and Neisseria species, bind to dental pellicle and facilitate subsequent colonization by F nucleatum , which functions as a bridging species between early and late colonizers. 235 From approximately 18 hours to 4 days following colonization of dental biofilm, primary colonizers remain the predominant species among biofilm communities.…”
Section: Plaque Formation and Periodontal Diseasementioning
confidence: 99%
“…Primary colonizers of dental biofilm with specific adhesion factors form weak, long‐range physicochemical interactions with the pellicle to facilitate receptor‐mediated binding 235,236 . Primary colonizers are primarily gram‐positive cocci and rods, especially Streptococcus species, such as S salivarius 237 . Traditional models of microbial biofilm succession follow a sequential process in which the initial attachment of primary colonizers, namely Streptococcus, Actinomyces, Gemella, Veillonella, Rothia, and Neisseria species, bind to dental pellicle and facilitate subsequent colonization by F nucleatum , which functions as a bridging species between early and late colonizers 235 .…”
Section: Plaque Formation and Periodontal Diseasementioning
confidence: 99%
“…The oral environment is the richest and most varied in terms of the presence of microorganisms. Within the oral cavity, there are several distinct environments in which different microbial communities are present [ 25 , 26 , 27 ]. Recently published review reports indicate that more than 700 bacterial species have been identified by culture-independent approaches in the human oral cavity while over 250 of them have been described and named [ 28 ].…”
Section: Microbial Flora and Biofilm Formation In Oral Environmentmentioning
confidence: 99%
“…For example, the inflammatory response of epithelial cells to different bacterial species may be compared [16] or different eukaryotic cell lines may be challenged with the same oral pathogenic species, such as Porphyromonas gingivalis (P. gingivalis), a key contributor to the pathogenesis of periodontitis [19]. However, it is known that interactions between [92]). (b) Cells and tissue types present in the oral mucosa, demonstrating complexity of 3D structure.…”
Section: D Cell Culturementioning
confidence: 99%
“…
Figure 1. (a) Common bacterial species present in pathogenic oral biofilms and their communication between species (adapted from Parashar et al [ 92 ]). (b) Cells and tissue types present in the oral mucosa, demonstrating complexity of 3D structure.
…”
Section: Introductionmentioning
confidence: 99%